Prevalence of axial spondyloarthritis in patients with inflammatory bowel disease using cross-sectional imaging: a systematic literature review. (March 2021) - Evans, Jobie; Sapsford, Mark; McDonald, Scott; Poole, Kenneth; Raine, Tim; Jadon, Deepak R.
Background: Patients with inflammatory bowel disease (IBD) have an excess burden of axial spondyloarthritis (axSpA), which, if left untreated, may significantly impact on clinical outcomes. We aimed to estimate the prevalence of axSpA, including previously undiagnosed cases, in IBD patients from studies involving cross-sectional imaging and identify the IBD features potentially associated with axSpA. Methods: PubMed, Embase and Cochrane databases were searched systematically between 1990 and 2018. Article reference lists and key conference abstract lists from 2012 to 2018 were also reviewed. All abstracts were reviewed by two authors to determine eligibility for inclusion. The study inclusion criteria were (a) adults aged 18 years or above, (b) a clinical diagnosis of IBD and (c) reporting identification of sacroiliitis using cross-sectional imaging. Results: A total of 20 observational studies were identified: 12 used CT, 6 used MR and 2 utilised both computed tomography (CT) and magnetic resonance (MR) imaging. Sample sizes ranged from 25 to 1247 (a total of 4096 patients); 31 studies were considered to have low selection bias, 13 included two or more radiology readers, and 3 included rheumatological assessments. The prevalence of sacroiliitis, the most commonly reported axSpA feature, ranged from 2.2% to 68.0% with a pooled prevalence of 21.0% [95% confidence interval (CI) 17–26%]. Associated IBD features include increasing IBD duration, increasing age, male sex, IBD location, inflammatory back pain and peripheral arthritis. No significant difference in the prevalence of sacroiliitis between Crohn's disease and ulcerative colitis was identified. Study limitations include variability in the individual study sample sizes and patient demographics. Conclusion: This review highlights the need for larger, well-designed studies using more sensitive imaging modalities and multivariable modelling to better estimate the prevalence of axSpA in IBD. An improved knowledge of the IBD phenotype(s) associated with axSpA and use of cross-sectional imaging intended for IBD assessment to screen for axSpA may help clinicians identify those patients most at risk.